Period prevalence and mortality rates associated with hypocholesterolaemia in dogs and cats: 1, 375 cases. (7th August 2020) - Tan, A. W. K.; Epstein, S. E.; Hopper, K.
Objectives: To determine the period prevalence of hypocholesterolaemia and the associated mortality rates in dogs and cats at a university teaching hospital. The secondary aim was to identify disease processes associated with hypocholesterolaemia. Materials and Methods: Medical records over a 5‐year period were reviewed to determine the severity of hypocholesterolaemia and its associated mortality rate. Medical records of animals with moderate to severe hypocholesterolaemia (<2.59 mmol/L in dogs, <1.81 mmol/L in cats) were analysed further. Animals with hospital‐acquired hypocholesterolaemia were identified. Results: Among 16, 977 dogs and 3, 788 cats that had at least one cholesterol measurement, the period prevalence of hypocholesterolaemia was 7.0% in dogs and 4.7% in cats. The mortality rate of hypocholesteraemic dogs and cats was 12% in both species which was significantly higher than that of animals with normal serum cholesterol. The degree of hypocholesterolaemia was significantly associated with mortality. Dogs, but not cats, with hospital‐acquired hypocholesterolaemia had a higher mortality rate than those presenting with hypocholesterolaemia. Disease of hepatic, gastrointestinal and lymphoreticular systems were most commonly associated with hypocholesterolaemia, and infectious and neoplastic disease were the most commonly associated pathophysiologic processes in both species. Lymphoma was over‐represented in dogs with neoplasia. Clinical Significance: Hypocholesterolaemia is not a frequent abnormality but was associated with mortality in this study and may be a negative prognostic indicator. It is not known if hypocholesterolaemia is simply a marker for disease severity, or if it is has active physiologic effects contributing to poor outcomes.